Phage vB_Kpn_HF0522: Isolation, Characterization, and Therapeutic Potential in Combatting K1 Klebsiella pneumoniae Infections - Yan T; Wang Q; Ma C; Teng X; Gong Z; Chu W; Zhou Q; Liu Z (Infection and Drug Resistance)
Tao Yan,1,2 Qiuyan Wang,2 Chengcheng Ma,2 Xuan Teng,2 Zhen Gong,2 Wenwen Chu,2 Qiang Zhou,2 Zhou Liu1 1Department of Clinical Laboratory Center, Anhui Chest Hospital, Hefei, 230031, People’s Republic of China; 2Department of Clinical Laboratory, the Second Affiliated Hospital of Anhui Medical University, Hefei, 230601, People’s Republic of ChinaCorrespondence: Zhou Liu, Department of Clinical Laboratory Center, Anhui Chest Hospital, Hefei, People’s Republic of China, Email liuzhou0112@ahmu.edu.cnPurpose: Klebsiella pneumoniae is a globally prevalent pathogen responsible for severe hospital- and community-acquired infections, and presents significant challenges for clinical management. Current therapeutic strategies are no longer able to meet the clinical needs; therefore, there is an urgent need to develop novel therapeutic strategies. This study aimed to evaluate the efficacy of phage therapy in treating bacterial infections.Methods: Isolated phage vB_Kpn_HF0522 and phage morphology were observed using transmission electron microscopy. Analysis of vB_Kpn_HF0522 characteristics, including optimal multiplicity of infection (MOI), one-step growth curve, host range, stability in different environments, and adsorption capacity. The phage genomic sequence was analyzed to explore evolutionary relationships. The effect of phage vB_Kpn_HF0522 on biofilms was assessed using crystal violet staining assay. The Galleria mellonella (G. mellonella) infection model and mouse infection models were established to evaluate the practical application potential of the phage and the fitness cost of phage-resistant bacteria.Results: Phage was isolated from hospital sewage for experimental studies. Genome analysis revealed that vB_Kpn_HF0522 is a double-stranded linear DNA virus. Biological characterization demonstrated that this phage specifically targets serotype K1 K. pneumoniae with an optimal multiplicity of infection (MOI) of 0.01, effectively disrupting biofilms and inhibiting bacterial growth. The bacterial growth rate remained largely unchanged after the phage resistance mutation, but mice infected with the mutant strain showed significantly higher survival rates than those infected with the wild-type strain. vB_Kpn_HF0522 increased the survival rate of infected G. mellonella from 12.5% to 75%, inhibited incisional surgical site infections and alleviated inflammatory response in mice.Conclusion: These findings indicate that vB_Kpn_HF0522 has significant potential for treating specific bacterial infections, and may serve as an antimicrobial agent for research and clinical anti-infective therapy.Keywords: phage vB_Kpn_HF0522, phage therapy, Klebsiella pneumoniae, phage resistance, incisional surgical site infection, biofilm